Dinamika Populisme di Era Digital: Pengaruh Media Sosial Terhadap Pemikiran Politik Masyarakat - Junaeda, St; Khaerunnisa (Journal of Education and Culture, 2024)
Populism has become a significant global political phenomenon in an increasingly connected digital age. The study explores the dynamics of populism in social media and its influence on public political thinking. We used analytical methods to explore how social media platforms strengthen populist narratives and influence public political perceptions and studies. Through literature analysis and library studies, we found that populist leaders can use social media as an effective way to convey their message directly to the wider masses. It gives them an opportunity to strengthen their identities, emphasize controversial issues, and gain emotional support. However, the negative consequence of this phenomenon is the spread of false or false information, which can increase political polarization and social fragmentation. We stress the importance of gaining a better understanding of the mechanisms that drive change in public opinion in the digital world as well as the elements that trigger populism. With this understanding, more effective strategies could be developed to control the negative effects of populism on social media and encourage critical thinking as well as constructive conversations among communities.